Topology synthesis of integrated active power decoupling converters using asymmetrical H-bridge circuits - Liu, Yonglu; Zuo, Yiqi; Yuan, Liang (Frontiers in Electronics, 2023)
Aiming to handle the inherent double-line frequency ripple power in single-phase power systems, a lot of the active power decoupling (APD) topologies have been developed. In this paper, a general way to synthesize APD topologies is introduced. The main construction idea is to insert a rectifier/inverter into asymmetrical H-bridge circuits (AHCs) or replace the switch/diode in the AHCs with a rectifier/inverter. This construction idea can reveal the formation process of existing APD topologies and deduce new APD topologies. Finally, an experimental case study has been carried out to illustrate the feasibility and effectiveness of the proposed topology synthesis method.